Application of SA-PSO Algorithm in Parameter Optimization of Dynamic Vibration Absorber. Issue 4 (May 2019) - Zhe-ming, Chen; Peng, Wang; Jiang-hua, Fu; Bao, Chen
Abstract: Focus on the noise problem in a 7-segment midsize SUV in the condition of wide open throttle in gear 2, noise testing and finite element analysis were combined to analyze the problem, and it was found that there was a significant resonance band around the frequency of 214 Hz, which was particularly evident under the fourth-order excitation. The frequency of resonance band is close to the second-order modal natural frequency of the sub-frame, The resonance band needs to be eliminated to reduce the noise inside the car. Adopting the scheme of installing a dynamic vibration absorber on the sub-frame to make the second-order modal of the sub-frame avoids the resonance frequency. The simulated annealing algorithm is combined with the particle swarm optimization algorithm to optimize the parameters of the dynamic vibration absorber. A dynamic vibration absorber was designed with optimized parameters and verified by simulation and installed on the car. It was verified that The designed dynamic vibration absorber eliminates the 214Hz resonance band and obviously reduce the noise inside the car.